2010
DOI: 10.1080/09669581003668516
|View full text |Cite
|
Sign up to set email alerts
|

Identifying tourists with smaller environmental footprints

Abstract: This paper identifies which information about tourists serves as the best predictor of their pro-environmental behavior at home and on vacation. If a small set of predictors can be identified, the tourism industry would be able to use them to focus attention on attracting tourists with smaller environmental footprints. Results from a survey asking respondents about pro-environmental behavior in their role as residents and tourists indicate that environmental concern, altruism, feeling morally obliged to behave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
3
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 52 publications
(71 reference statements)
10
110
3
7
Order By: Relevance
“…This view is endorsed by Dolnicar's (2010) research that observed that people who consider themselves as eco-friendly would behave in a pro-environmental way if they had the opportunity to do so, even on vacations. Behavioural control (beliefs about the presence of factors that facilitate performance of the behaviour) enables individuals to move from attitudes to actual behaviour (Berger & Corbin, 1992).…”
Section: The Impact Of Management Strategies Benefits and Barriers Omentioning
confidence: 82%
See 1 more Smart Citation
“…This view is endorsed by Dolnicar's (2010) research that observed that people who consider themselves as eco-friendly would behave in a pro-environmental way if they had the opportunity to do so, even on vacations. Behavioural control (beliefs about the presence of factors that facilitate performance of the behaviour) enables individuals to move from attitudes to actual behaviour (Berger & Corbin, 1992).…”
Section: The Impact Of Management Strategies Benefits and Barriers Omentioning
confidence: 82%
“…Prior research has demonstrated that people are more likely to become involved in a good cause if they are asked in advance to do so (Schwarzwald, Raz, & Zvibel, 1979;Sherman, 1980), and if facilities are provided to enable their involvement (Dolnicar, 2010;McKenzie-Mohr, 2000b;Schwarzwald, Raz, & Zvibel, 1979;Sherman, 1980). Thus, festivals that request eco-friendly behaviours in their attendees before and during the festival or, in other words, frame the event as green, seem to be more effective in controlling negative environmental impacts than those festivals that do not.…”
Section: Attendees' Perceptions Regarding the Green Status Of The Fesmentioning
confidence: 99%
“…Barber et al identified the market of "the Millennial male with strong environmental attitudes" as a "substantial market for ecological products" (Barber et al, 2010, p. 64). Dolnicar (2010) found environmental values, or a moral obligation to protect the environment, was a strong predictor of environmentally-friendly tourist behavior and environmental behavior at home. Ham and Han (2012) show that purchase-related loyalty, measured as intentions to visit, acceptance of price premiums, and providing recommendations, were amplified by consumers with positive environmental values.…”
Section: Environmental Valuesmentioning
confidence: 99%
“…• the analysis of the behavior and motivations of the segments of demand that are interested in sustainable tourism offers [37,[53][54][55][56][57][58][59][60].…”
Section: Sustainable Tourism and Tourist Demandmentioning
confidence: 99%